2017
DOI: 10.1186/s13019-017-0614-4
|View full text |Cite
|
Sign up to set email alerts
|

Smoking and timing of cessation on postoperative pulmonary complications after curative-intent lung cancer surgery

Abstract: BackgroundSmoking is a risk factor for postoperative pulmonary complications (PPC) following non-small cell lung cancer (NSCLC) surgery. The optimal timing for preoperative smoking cessation has not been identified. Our study aimed to observe the impact of preoperative smoking cessation on PPC incidence and other postoperative outcomes including long-term survival.MethodsA prospective study included consecutive patients following resection for NSCLC in a regional thoracic centre over a 4-year period (2010–2014… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
5
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 83 publications
(60 citation statements)
references
References 29 publications
2
51
5
2
Order By: Relevance
“…Smoking cessation before surgery can reduce postoperative complications [33]. The difference in pneumonia occurrence between current smokers and ex-smokers was not apparent in our study.…”
Section: Discussioncontrasting
confidence: 67%
“…Smoking cessation before surgery can reduce postoperative complications [33]. The difference in pneumonia occurrence between current smokers and ex-smokers was not apparent in our study.…”
Section: Discussioncontrasting
confidence: 67%
“…Smoking cessation before surgery can reduce postoperative complications [28]. The difference in pneumonia occurrence between current smokers and ex-smokers was not apparent in our study.…”
Section: Discussioncontrasting
confidence: 67%
“…An earlier study suggested an increased risk of PPC in patients who stop smoking within 4 weeks of thoracotomy and lung resection [ 24 ], though this study was limited by its retrospective design and has since been superseded. More recent evidence has shown that the risk of PPC after thoracotomy reduces with smoking cessation, but no optimal time can be defined [ 25 , 26 ]. Currently in the UK there is no integrated preoperative smoking cessation service in thoracic surgery, as only community based cessation services exist.…”
Section: Discussionmentioning
confidence: 99%